Retrograde maxillary nerve perineural injection: A tomographic and anatomical evaluation of the infraorbital canal and evaluation of needle type and size in equine cadavers. (November 2016) - Nannarone, S.; Bini, G.; Vuerich, M.; Menchetti, L.; Arcelli, R.; Angeli, G.
Highlights: The equine infraorbital canal was fully examined by computed tomography and dissection. Different needles were tested within the infraorbital foramen (IF). A simulation of the maxillary nerve block approached at the IF was investigated. Abstract: The aim of this study was to investigate a new approach for equine maxillary nerve blocks, which can facilitate several orofacial surgeries. Current techniques aim at the maxillary foramen and approach via the zygomatic arch, conferring the risk of injury to several delicate structures in the target area. To investigate the feasibility of a retrograde approach from the infraorbital foramen, an anatomic study of the infraorbital canal and its surrounding structures was performed on 13 cadaveric skulls using computed tomography and anatomical dissection. Measurements included canal length and volume, its conformation and relationship with the enclosed structures, and infraorbital foramen diameters. The technical approach to simulate the distribution of local anaesthetic within the infraorbital canal was further defined, including needle selection among seven different needles, evaluating ease of insertion, trauma to surrounding tissues and spread of contrast medium toward the target area. To validate the technique, two Tuohy needles were randomly inserted at 12 infraorbital foramina and 10 mL of contrast medium was injected. CT verified the spread of the solution and possible complications. Each canal had a serpentine-curved pathway. Anatomical dissections evidenced gaps between the infraorbital nerve, vessels and the infraorbital canal. The integrity of these structures had been preserved from the passage of the selected Tuohy needles. This study suggests a feasible approach to the maxillary nerve block within the infraorbital canal providing an appropriate needle selection and technique to limit complications.